Impacto e destinação dos celulares retornados ao fabricante, no mercado brasileiro - Franzini, Carlos Eduardo (2019)
With the rapid obsolescence due to technology and advances in the electronic segment, especially for mobile devices, which evolve in design and technology, many devices are returned to manufacturers for various reasons, considering several reasons such as end of life, warranty, buyback (is slaughtered in the purchase of a new one), return of the commerce etc. Due that, manufacturers need a process for the definition and destination of these returns, which is analyzed in this work, for cellular devices. The objective of this work is to carry out a case study in a cellular refurbishment company to evaluate the impact and destination of returned cellular phones to the manufacturer in the Brazilian market. The case study was conducted through an interview in a company, which is responsible for the returns and destination of the returned cell phones of a large electronic brand, where the destination and refurbishment / requalification are practiced. As result the specific and general objectives were achieved and the propositions were confirmed in the study. It is concluded that the refurbishment process is of great importance for the whole chain, considering manufacturer, refurbishment company, labor market, consumer and environment, since products with good quality are offered, where guarantee is applied for them and with lower cost in relation to new products, making the refurbishment generate revenue for the manufacturer, profit the refurbishment company, jobs, attractive prices and finally, avoids the annual discard of approximately 4.5 tons of material applied to the appliances and the material not recovered volume disposed of properly, through the recycling process through a qualified company.